Genome-wide association studies in lung disease. Issue 3 (19th August 2011) - Soler Artigas, María; Wain, Louise V; Tobin, Martin D
Abstract : Genome-wide association studies (GWAS) have provided new insights into the molecular mechanisms of lung function and lung diseases. GWAS, and studies that build upon their findings, will continue to provide evidence aimed at advancing understanding of lung disease. This paper summarises the key features of a GWAS, references some recent findings and discusses how the chest physician can interpret the validity and utility of future GWAS and related studies.